KARAKTERISTIK PENDERITA DIABETES MELLITUS DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT MARTHA FRISKA TAHUN 2014 - riris lumban; Hiswani .; Taufik Ashar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTDiabetes Mellitus (DM) is a degenerative disease with a prevalence continue toincrease from year to year. Based on data Riskesdas 2013, the national prevalence ofdiabetes mellitus in 2007 was 1,1%, increase in 2013 to 2,1%.This study was aim to know the characteristics of patients DM with complicationsadmitted to the Martha Friska Hspital in 2014, descriptive study has been done by using caseseries design. The population were 835 DM patient data, sample were 101 DM patient data,by using simple random sampling technique.The results showed the proportion of patients with complications of DM was highestin the age group 61-70 years (35.7%), female (57.4%), batak (52.5%), PNS/BUMN (38.7%),high school (64.3%), in Medan (70.3%), type 2 DM (99.0%),dyspepsia complication (55,4%),chronic complications (83.1%),without HbA1C test (86,1%), HbA1C levels are not controlled(78,6%), hypoglycemic oral medicine (84.2%), health assurance (84.2%), average length ofstay (7 days), becoming outpatient (71.3%). According to statistic,there was no differencebetween the proportion of age based categories of complications (p = 0.239), gender basedcategories of complications (p = 0.454), treatment with categories of complications (p =0.588) and long treatment by category of complications (p = 0.918). There is a relationshipbetween the proportion of type DM by category complications (p = 0.024).It is suggested to the Martha Fiska Hospital to have HbA1C check for the patient andto improve education for patient especially DM complication. It is also suggested to DMpatient with complication to check glucose routine and HbA1C, to use insulin in curing andto apply health life style in controlling blood glucose.Keywords: Characteristic, Diabetes Mellitus with complication